PENYELENGGARAAN PROGRAM KESETARAAN PAKET C DI SKB MAROS - Rahman, Muh.Fadlul; Latif, M.Ali; Latang, Latang (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2023)
ABSTRACTThis study aims to determine the implementation of the package C equality program at SPNF SKB Maros. The subjects of this study were 4 tutors and 10 learning residents. The data in this study were collected by observation, interview and documentation techniques. Data is processed by data reduction, data presentation, as well as conclusions and verification. The results of the study show that this study examines the Package C equivalence program at SPNF SKB Maros through three stages, namely: Planning, namely by identifying prospective learning citizens by requiring that they have learning needs in participating in the Package C program equivalent to SMA, then making RPP and Syllabus; the implementation of learning using varied learning methods, the time of learning 3 times a week and the place of implementation of learning in the SPNF SKB Maros study room; assessment instruments using tests and observation guidelines, assessment reports are made at the end of learning.Key words: Package C equivalence program, Learning Needs